Effect of the timing of the pole plant on energy loss in the pole vault take-off - Linthorne, N. P. (ISBS Proceedings Archive (Michigan), 2018)
Some leading pole vault coaches recommend a late planting of the pole, at close to the instant of take-off. This technique is believed to reduce the energy lost during the take-off and produce a higher vault. The present study re-analysed data from a previous study in which male pole vaulters manipulated the timing of the pole plant. An individual analysis showed that the timing of the pole plant did not clearly affect the change in the total energy of the athlete/pole system during the take-off. This result suggests there might be no advantage in using a late pole plant. An individual analysis can sometimes be more likely to yield a true interpretation of experimental data than a group analysis.